2022
DOI: 10.1038/s41467-022-34765-w
|View full text |Cite
|
Sign up to set email alerts
|

How Carvedilol activates β2-adrenoceptors

Abstract: Carvedilol is among the most effective β-blockers for improving survival after myocardial infarction. Yet the mechanisms by which carvedilol achieves this superior clinical profile are still unclear. Beyond blockade of β1-adrenoceptors, arrestin-biased signalling via β2-adrenoceptors is a molecular mechanism proposed to explain the survival benefits. Here, we offer an alternative mechanism to rationalize carvedilol’s cellular signalling. Using primary and immortalized cells genome-edited by CRISPR/Cas9 to lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 142 publications
2
24
0
Order By: Relevance
“…In a separate study, we have used the protocol for an extensive study of the β 2adrenergic receptor with similar success to that reported here for 5-HT 1A , and very recently, a paper was published reporting A 100 free-energy profiles to support experimental data. 34 Given that A 100 is rapidly gaining acceptance as a general activation measure, 33 and considering the reliability of the optimized protocol described here, we are confident to have described a metadynamics simulation technique that is superior to other activation CVs, for instance, the TM3−TM6 distance, as described above.…”
Section: ■ Results and Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…In a separate study, we have used the protocol for an extensive study of the β 2adrenergic receptor with similar success to that reported here for 5-HT 1A , and very recently, a paper was published reporting A 100 free-energy profiles to support experimental data. 34 Given that A 100 is rapidly gaining acceptance as a general activation measure, 33 and considering the reliability of the optimized protocol described here, we are confident to have described a metadynamics simulation technique that is superior to other activation CVs, for instance, the TM3−TM6 distance, as described above.…”
Section: ■ Results and Discussionmentioning
confidence: 84%
“…19 The A 100 index was initially introduced as an analysis tool, and its use as a CV has been very recently reported to support experimental data rationalizing carvedilol's cellular signaling in the β 2 -adrenergic receptor. 34 Here, we define the computational protocol exactly and describe its application to the serotonin 5-HT 1A receptor in its apo-form (ligand-free) and in the presence of two known ligands: the full agonist serotonin and the partial agonist aripiprazole. Apart from its simple definition and general applicability, further advantages of using A 100 with multiple walkers metadynamics are that no a priori knowledge of either the active or the inactive state is required, nor an initial path connecting the two states.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This compound interfered with the effects of the β-AR blocker carvedilol. Cmpd-6, on the one hand, increased the affinity of carvedilol for β 2 -AR and thereby enhanced its inhibitory effect on β 2 -agonist-induced stimulation of G s -proteins and cAMP signaling and, on the other hand, enhanced the stimulatory effects of carvedilol on ERK1/2 activity, endocytosis of β 2 -Ars, and their trafficking into lysosomes [ 426 ], which, as was shown later, is also due to the activation of G s -proteins [ 427 ].…”
Section: Allosteric Regulators Of β-Adrenergic Receptorsmentioning
confidence: 99%